(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
To bridge the gap between the worlds of circuit design and chip fabrication, SPICE (Simulation Program with Integrated Circuit Emphasis) models have emerged as a critical player. The program is integrated into electronic engineering to simulate the problematic principles of analog modulation using superb free simulation software. The present study examined the role of the Pspice simulation program in developing engineering students' circuit design skills. The study participants included one hundred and eighty-seven (n = 187) students in the electrical engineering department at Edo State Polytechnic in Usen, Edo State, Nigeria. The participants' ages ranged from 23 to 31 years old, with a mean age of (M=9.14) and a standard deviation of (SD=1.24). They were separated into two groups, with group (A) as the experimental condition. On the other hand, group (B) is the condition that serves as the control. A t-test analysis was performed on the data to answer the research question of whether the Pspice simulation software would increase students' skills in circuit design. The research found that circuit design skills were significantly different under the experimental settings compared to the control conditions (MD = 5.08, t (185) = 7.328, p =.000). Consequently, the findings answered the study's research question. The finding suggests that SPICE might be utilized to enhance students' circuit design skills. Implications and suggestions for application are presented.